Трудова дисципліна та методи її забезпечення - Коваленко, К. В.; Kovalenko, K. V.; ORCID: http://orcid.org/0000-0002-2105-9664; ResearcherID: J-7803-2016 (Право і безпека. – 2017. – № 3 (66). – С. 98–102, 2017)
Висвітлено правові засади та особливості правового регулювання трудової дисципліни й методів її забезпечення взагалі та службової дисципліни зокрема. На підставі аналізу досліджень провідних науковців та нормативно-правових актів визначено сутність «трудової дисципліни» як багатоаспектного явища. Акцентовано увагу на необхідності внесення змін до проекту Трудового кодексу України № 1658. Проаналізовано положення проекту закону України № 4670 «Про Дисциплінарний статут Національної поліції України» щодо правового регулювання службової дисципліни та методів її забезпечення.

The legal principles and peculiarities of legal regulation of labor discipline and methods of its provision in general and the service discipline in particular have been highlighted. Some gaps in the legal regulation of labor discipline and methods of its provision have been outlined in both current legislation and drafts of new regulatory acts. It has been noted that special importance is the necessity to study labor discipline and methods of its provision for the adoption of the Labor Code of Ukraine and new regulatory acts, which should regulate labor relations in view of the modern needs of the society. On the basis of the analysis of research by leading scholars and regulatory acts, the author has defined the essence of “labor discipline” as a multidimensional phenomenon. The emphasis is paid to the necessity of amending the draft of the Labor Code of Ukraine No. 1658 and consolidating the notion, general principles and methods of ensuring and observing labor discipline in the first book “General Provisions”. It has been offered to amend the Art. 273 “Ensuring the compliance with labor discipline” of the draft of the Labor Code of Ukraine No. 1658 in the new wording, supplementing it by the instruction on the use of the coercion method in ensuring labor discipline. The author has analyzed the provisions of the draft of the Law of Ukraine No. 4670 “On the Disciplinary Statute of the National Police of Ukraine” regarding the legal regulation of the service discipline of the officers of the National Police of Ukraine and the methods of its provision. It has been noted that labor discipline concerns not only the sole responsibility of the parties of labor relations. It is provided by various methods and is connected with various institutions of labor law. Therefore, the concept, general principles and methods of ensuring and observance of labor discipline should be laid down in the first book “General Provisions” of the draft of the Labor Code of Ukraine No. 1658.

Освещены правовые основы, особенности и определённые пробелы правового регулирования трудовой дисциплины и методов её обеспечения вообще и служебной дисциплины в частности. На основании анализа исследований ведущих учёных и нормативно-правовых актов определена сущность трудовой дисциплины как многоаспектного явления. Акцентировано внимание на необходимости внесения изменений в проект Трудового кодекса Украины № 1658. Проанализированы положения проекта закона Украины № 4670 «О Дисциплинарном уставе Национальной полиции Украины».
Трудовая дисциплина и методы её обеспечения
Labor discipline and methods of its provision
Коваленко, К. В. Трудова дисципліна та методи її забезпечення / К. В. Коваленко // Право і безпека. – 2017. – № 3 (66). – С. 98–102.
Kovalenko, K.V. (2017), “Labor discipline and methods of its provision” [“Trudova dystsyplina ta metody yii zabezpechennia”], Pravo i Bezpeka, No. 3, pp. 98–102.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; трудова дисципліна; методи забезпечення трудової дисципліни; службова дисципліна; labor discipline; methods of ensuring labor discipline; service discipline; трудовая дисциплина; методы обеспечения трудовой дисциплины; служебная дисциплина